Comparative study between an intensive small group teaching and a 1-year clinical practice on OSCE - Kim, Sinjae; Park, Minhwan; Seo, Ji-Hyun; Woo, Hyang-Ok; Youn, Hee-Shang; Park, Jung Je; Jeon, Sea-Yuoug; Hwa, Jung Seok; Mullan, Patricia; Gruppen, Larry D. (Kosin Medical Journal (Online), 2018)
Our school introduced a new curriculum based on faculty-directed, intensive, small-group teaching of clinical skills in the third-year medical students. To examine its effects, we compared the mean scores on an OSCE between the third- and fourth-year medical students. Methods Third- and fourth-year students did rotations at the same five OSCE stations. They then completed a brief self-reporting questionnaire survey to examine the degree of satisfaction with new curriculum in the third-year students and clinical practice in the fourth-year students, as well as their perception of confidence and preparedness. We analyzed the OSCE data obtained from 158 students, 133 of whom also completed the questionnaire. Results Mean OSCE scores on the breast examination and wet smear stations were significantly higher in the third-year group (P < 0.001). But mean OSCE scores of motor-sensory examination and lumbar puncture were significantly higher in the fourth-year group (P < 0.05). The mean OSCE scores had no significant correlation with satisfaction. In addition, the self-ratings of confidence had a high degree of correlation with satisfaction with new curriculum (r = 0.673) and clinical practice (r = 0.692). Furthermore, there was a moderate degree of correlation between satisfaction and preparedness in both groups (r = 0.403 and 0.449). Conclusions There is no significant difference in the effect on the degree of clinical performance and confidence between an intensive-small group teaching and a 1-year clinical practice. If combined, intensive small group teaching and clinical practice would be useful to improve the degree of ability and confidence in medical students.